2013
DOI: 10.1007/s00359-013-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Cattle on pastures do align along the North–South axis, but the alignment depends on herd density

Abstract: Alignment is a spontaneous behavioral preference of particular body orientation that may be seen in various vertebrate or invertebrate taxa. Animals often optimize their positions according to diverse directional environmental factors such as wind, stream, slope, sun radiation, etc. Magnetic alignment represents the simplest directional response to the geomagnetic field and a growing body of evidence of animals aligning their body positions according to geomagnetic lines whether at rest or during feedings is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…They attacked our results (Hert et al 2011), but we could show ) that their study was heavily flawed and cleaned of errors it actually fully confirmed our original findings. Our results were subsequently confirmed in an independent study by Slabý et al (Slaby, Tomanova, and Vacha 2013). In other studies we found magnetic alignment in hunting foxes , carps schooling in circular tubs (Hart et al 2012), and mallard ducks landing on water (Hart et al 2013).…”
supporting
confidence: 80%
“…They attacked our results (Hert et al 2011), but we could show ) that their study was heavily flawed and cleaned of errors it actually fully confirmed our original findings. Our results were subsequently confirmed in an independent study by Slabý et al (Slaby, Tomanova, and Vacha 2013). In other studies we found magnetic alignment in hunting foxes , carps schooling in circular tubs (Hart et al 2012), and mallard ducks landing on water (Hart et al 2013).…”
supporting
confidence: 80%
“…There is no reason, however, to expect any collective behaviour in songbirds that mainly migrate alone. We furthermore see the possibility of using the same laboratory approach in other taxa to investigate whether alignment behaviour is affected by, for example, group density (Slaby et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Following this first finding, a growing number of studies have been published around this topic (Begall et al, 2013, and references therein) with the most recent studies largely focusing on vertebrates (e.g. Hart et al, 2013aHart et al, , 2013bSlaby et al, 2013;Malkemper et al, 2015;Obleser et al, 2016;Čapek et al, 2017;Nováková et al, 2017;. The adaptive significance of magnetic body alignment remains elusive (Begall et al, 2013), and only in a few cases is there some support for plausible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdavi et al [49,51] have reported that exposures to electromagnetic fields with 5 Hz or 12 Hz elevated activity levels and adrenocorticotropic hormone concentrations in rats. Additionally, there have been reports that cattle aligned their body axes along geomagnetic field lines, which indicates they have the sense of magnetoreception [54,55,56]. To verify this hypothesis, observations of daily cow milk yields and ULF radiation from the same period in the same region need to be performed.…”
Section: Discussionmentioning
confidence: 99%